Pengaruh Gaya Kepemimpinan Pacesetting Terhadap Motivasi Kerja Karyawan F & B Service Departement Pada Sintesa Peninsula Hotel Manado - Seska Meily Hermin Mengko (PolimdoSains, 2020)
Abstract: The Influence of Pacesetting Leadership Style on Work Motivation of Food and Beverage Service Department Employees at Sintesa Peninsula Hotel Manado. Employees with high work motivation will work with passion, discipline, initiative and with an awareness of their obligations to work more effectively and efficiently. With the existence of motivation, the thought, the attention, energy and activities of employees can be directed to reach the goals and objectives that are more useful and beneficial for the company and the employees themselves. High motivation in work can be achieved if it supported by a leadership style that is owned and applied by leaders in an organization or department. Leadership style applied by Food and Beverage Service Department leaders requires high standards of work and success, hopes that employees can follow the standard of work, but lack of appreciation that employees get in achieving their jobs, low employee freedom to take initiatives that will reduce challenges in the workplace, it has an impact on changes in work motivation of employees. Based on these problems, a study was conducted to determine whether the pacesetting leadership style had an effect on the work motivation of the employees of the Food and Beverage Service Department. This type of research is a quantitative study with a sample of 30 respondents. The results of the study stated that there is a strong influence of the Pacesetting Leadership Style variable on the Employee Work Motivation variable with a significance value of 0,000 < 0.05 and t count value of 5.360 > t table 2.04841, obtained a correlation value of r = 0.712 and the coefficient of determination 50.69%, the rest 49.31% is influenced by other factors not examined. As an implication of the results of this study is that leaders need to provide the opportunities for employees to take the initiative in the work they do and be more flexible in each direction given so that employees are able to complete their work properly. To increase employee motivation, leaders need to inspire employees to work optimally, provide challenges in work, and be able to appreciate employees for work completed by employees.